2020
DOI: 10.1097/md.0000000000021248
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Zuojin Pill for chronic gastritis

Abstract: Background: Chronic gastritis (CG), as the highest incidence of gastrointestinal diseases, has been gradually increasing around globally. With the obvious disadvantages of standard treatment, more and more people ask the traditional Chinese medicine for help in the treatment of CG. As a traditional Chinese medicine compound, Zuojin Pill (ZJP) has a long history of clinical application in the treatment of digestive system diseases. Whereas, neither systematic nor meta-analysis of randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As a representative prescription in traditional Chinese medicine, ZJP exhibits functions such as inhibiting gastric acid secretion and exerting anti-ulcer and antibacterial effects, effectively ameliorating severe gastrointestinal reactions in patients. 8,14,15 Although ZJP holds therapeutic potential for UC, its mechanism remains incompletely elucidated. ZJP has been established to regulate intestinal flora and Treg cells, along with their subsets, and exert anti-oxidative stress effects in the treatment of UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a representative prescription in traditional Chinese medicine, ZJP exhibits functions such as inhibiting gastric acid secretion and exerting anti-ulcer and antibacterial effects, effectively ameliorating severe gastrointestinal reactions in patients. 8,14,15 Although ZJP holds therapeutic potential for UC, its mechanism remains incompletely elucidated. ZJP has been established to regulate intestinal flora and Treg cells, along with their subsets, and exert anti-oxidative stress effects in the treatment of UC.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Esteemed for its safety, efficacy, and prevention of disease recurrence, ZJP has found extensive utility in clinical practice and boasts a clinical therapeutic history spanning over 600 years. 8 Multiple studies have substantiated the efficacy of ZJP in addressing UC 9,10 ; however, the precise mechanistic basis of its therapeutic action in UC remains incompletely elucidated. In recent years, network pharmacology, employing a holistic research paradigm characterized by "multi-component-multi-targetcomplex disease," has provided preliminary insights into the mode of action of traditional Chinese medicine in disease treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research studies have shown that ZJP has a good therapeutic effect on gastric ulcer [4], ulcerative colitis [5], and other diseases. A meta-analysis based on a systematic review highlights that ZJP is effective and safe for chronic gastritis [6]. Our previous studies [7] showed that ZJP could ameliorate the injury of GES-1 and MNNG-induced CAG rats.…”
Section: Introductionmentioning
confidence: 98%